Fluorescent Coumarin-based Probe for Detection of Biological Thiols - Szwaczko, Katarzyna (Current Organic Chemistry, 2023)
Nature-derived thiols such as cysteine, homocysteine, and reduced glutathione play diverse and important roles in both plant and animal cells. In plants, they maintain redox homeostasis and affect photosynthesis and signal transduction processes. In animals, changes in the levels of biothiols have been linked to cardiovascular disease, Alzheimer's disease, neuropsychiatric disorders, or stroke. The detection of biothiols in biological samples is, therefore, very important. For this purpose, rapid, sensitive, and non-invasive methods for their sensing in living cells are highly desirable.This perspective reviews the past five years of advances in coumarin fluorescent probes for biothiol detection. The design of the probes, the mechanisms of thiol detection, and the applications in live cell imaging are presented. The classification of probes based on the coumarin backbone was made on the basis of the mode of their interactions with the analyte.
Keywords: Michael addition